Analisis Faktor yang Berhubungan dengan Rendahnya Capaian Pengelolaan Air Bersih dan Higiene Sanitasi di Puskesmas Selaparang Kota Mataram - Rizal Smith; Lalu Sulaiman; Akhmad Fathoni (Bioscientist : Jurnal Ilmiah Biologi, 2024)
The existence of infrastructure at the Public Health Center must be supported by governance including planning management, implementation, operational procedures, human resources, budgeting and infrastructure that have been determined so that the management of service units for the Public at the Public Health Center is in accordance with the standards set by the Ministry of Health. influencing the water and sanitation hygiene facility improvement tool (WASH FIT) assessment in public Health Centers throughout the city of Mataram in 2022 with the lowest results in the Selaparang public Health Center ( 63.05%). So it is necessary to analyze factors related to the low achievement of clean water management and sanitation hygiene at the Selaparang Public Health Center, Mataram City. This research is a qualitative descriptive method, namely providing a direct and comprehensive description at Public Health Center in Mataram City. Based on the research results, it shows that the condition of clean water management and sanitation hygiene from planning management, implementation, standard operating procedures, human resource guidelines, budget and infrastructure still has many deficiencies. Selaparang Public Health Center has not implemented planning management for clean water and sanitation hygiene in a truly open manner based on needs and has not involved sanitation and clean water officers, which has an impact on the implementation of WASH which is still lacking in operations, complete SOPs are not available, which impacts on poor compliance , sanitation and clean water program holders who are not involved in planning also result in inadequate budgets for the provision of adequate infrastructure, insufficient sanitation and clean water personnel do not meet needs due to transfers and permanent illness so that the workload becomes more and heavier. From these results, the implementation of sanitation and clean water at the Selaparang Public Health Center does not meet the standards in accordance with the Regulation of the Minister of Health of the Republic of Indonesia Number 2 of 2023 concerning Implementing Regulations of Government Regulation Number 66 of 2014 concerning environmental health and Regulation of the Minister of Health of the Republic of Indonesia Number 43 of 2019 concerning Public Health Centers, with the results of this research, the Regional Head needs to make a policy, the head of the Mataram City Health Service and the Head of the Public Health Center need to review planning, SOPs, meeting needs and increasing the capacity of officers, increasing the budget through more objective planning through guidance to environmental health program managers and officers sanitation.